Indigenous Archaeology in Sweden : Aligning Contract Archaeology with National and International Policies on Indigenous Heritage - Knutson, Charina (Linnéuniversitetet, Institutionen för kulturvetenskaper (KV), 2024)
This doctoral thesis examines the challenges and potential improvements in managing archaeological projects related to the Sámi people in Sweden. The focus is on aligning practices of contract archaeology with national and international policies for managing Indigenous cultural heritage. The research identifies five key challenges in Swedish archaeology: defining Sámi heritage sites, determining responsibility for relevant expertise, managing Sámi-related information, establishing processes of contract archaeology acceptable to all stakeholders, and deciding whether Sámi and "Swedish" heritage should be managed together or separately. The study compares the approach in Sweden with practices in Norway and British Columbia, Canada, to explore potential solutions. Different systems for cultural heritage management are analysed alongside interviews with archaeologists, Indigenous community members, officials, and other stakeholders, to map success factors and pitfalls of Indigenous cultural heritage management. The study highlights the slow implementation of the United Nations Declaration on the Rights of Indigenous Peoples (UNDRIP) in Sweden and the lack of legislation ensuring Sámi involvement in archaeological projects. The research suggests that addressing these challenges will require re-evaluating current practices, including developing clearer guidelines for managing Sámi heritage sites, improving collaboration between archaeologists and Sámi communities, finding ways to include intangible aspects of cultural heritage within cultural heritage management, and potentially delegating more authority in cultural heritage management to the Sámi Parliament. The thesis concludes by proposing strategies to better align Swedish contract archaeology with national and international policies on Indigenous cultural heritage, emphasizing the need for a balanced approach that respects Indigenous rights while addressing concerns in archaeological practice. These recommendations aim to ensure that Sámi cultural heritage is ...